Comparison of Homogeneous and Heterogeneous Catalysts in Biodiesel Production from Pongamia pinnata Oil - Panpraneecharoen, S.; Punsuvon, V.; Puemchalad, C. (Asian Journal of Chemistry, 2015)
Biodiesel was prepared by transesterification of Pongamia pinnata (P. pinnata) oil using potassium hydroxide (KOH) as homogeneous catalyst and synthesized calcium methoxide [Ca(OCH3)2] as heterogeneous catalyst. The Ca(OCH3)2 was synthesized from quick lime and characterized by scanning electron microscopy, X-ray diffraction, attenuated total reflection fourier transform, energy dispersive X-ray spectroscopy and BET surface area analysis to evaluate its performance. The parameters affecting the fatty acid methyl ester (FAME) content such as catalyst concentration, methanol to oil molar ratio and reaction time were investigated. Under optimized reaction condition, it was found that the 99.5 % of FAME conversion using KOH catalyst was achieved with 11:1 of methanol to oil molar ratio, 1.50 % wt of catalyst amount and 1 h of reaction time. The Ca(OCH3)2 catalyst was obtained the 98.04 % of FAME conversion with 15:1 of methanol to oil molar ratio, 3 % wt of catalyst amount, 3 h of reaction time at 65 ± 0.5 ºC of reaction temperature and 750 rpm of stirring rate on both catalysts. The result of the % FAME conversion, which determined by 1H NMR, suggested that Ca(OCH3)2 was the promising heterogeneous catalyst in replacing conventional homogeneous catalyst.